General Responsivity Adherence in Juvenile Drug Treatment Court: Examining the Impact on Substance-Use Outcome. (January 2016) - Taylor, Liana R.
Although the number of juvenile drug treatment courts (JDTC) in operation has increased since the first JDTCs were implemented in the 1990s, research continues to lag regarding the effectiveness of the treatment interventions that are provided. The purpose of the present study was to explore how the risk-need-responsivity models' general responsivity principle could be used to inform the effectiveness of the interventions provided to 1, 176 participants in nine JDTCs in the United States. Responsivity adherence was measured using the number of general responsivity-adherent techniques included in each intervention. The results indicated that an increase in general responsivity adherence was associated with an increase in substance-use severity score, which suggests that the effect of the JDTC model on treatment outcomes could vary by the type of interventions provided to participants. In addition, the findings suggest the need to further specify adherence to the general responsivity principle, particularly among substance-involved juvenile offenders.